The Effect of a Crude Palm Oil–Derived Hybrid Coolant on the Corrosion Behavior of SPCC-Based Electro-Galvanized Steel - Istianto Budhi Rahardja; Azhar Basyir Rantawi; Hendra Saputera; Dody Dody; Kartika Tresya Mauriraya; Samsurizal Samsurizal (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2025)
Water-based cooling systems can promote corrosion of metal components, while conventional ethylene glycol coolants pose toxicity and environmental concerns. To address these issues, a novel coolant derived from crude palm oil (CPO) was evaluated for its corrosion behavior on SPCC-based electro-galvanized steel, a material commonly used in radiator applications. The coolant formulation consisted of glycerol, propylene glycol, a CPO-based component, and distilled water, blended to achieve a homogeneous mixture, with chemical analysis confirming three principal natural constituents accounting for nearly the entire formulation. Corrosion performance was assessed by static immersion of SECC samples in the CPO-derived coolant at ambient temperature for 336 h. No measurable weight loss was detected after immersion. SEM–EDS analysis revealed a predominantly zinc-rich surface with no evidence of Fe-rich oxide formation, while XRD patterns were dominated by metallic Zn and Fe reflections at 2θ ≈ 44.6°, 65.2°, and 82.38°, with no diffraction peaks corresponding to crystalline iron corrosion products such as hematite, magnetite, or goethite. The absence of corrosion-related diffraction features and rust formation indicates that the CPO-based coolant did not induce corrosion under the investigated short-term conditions. These results suggest that the CPO-derived coolant is a promising renewable and corrosion-compatible alternative for cooling applications, although further evaluation under long-term, dynamic, and elevated-temperature conditions is required.